Eye Vergence Responses During an Attention Task in Adults With ADHD and Clinical Controls. Issue 9 (July 2021) - Jiménez, Elizabeth Carolina; Avella-Garcia, Claudia; Kustow, James; Cubbin, Sally; Corrales, Montse; Richarte, Vanessa; Esposito, Flavia Lorena; Morata, Imanol; Perera, Alexandre; Varela, Paloma; Cañete, Jose; Faraone, Stephen V.; et al.
Objective: ADHD patients show poor oculomotor control and recent studies show that attention-related eye vergence is weak in ADHD children. We aimed to assess vergence as a potential diagnostic biomarker for ADHD in adults.Method: We assessed the modulation in the angle of vergence while performing an attention task ( N = 144), comparing the results for adults previously diagnosed with ADHD ( N = 108) with age-matched clinical controls ( N = 36).Results: Significant differences in eye vergence response modulation between clinical controls and ADHD patients were documented. Diagnostic test accuracy was 79%.Conclusion: In combination with an attention task, eye vergence responses could be used as an objective marker to support the clinical diagnosis of adult ADHD.